Penerapan Manajemen Berbasis Sekolah untuk Meningkatkan Mutu Pendidikan di Sekolah Dasar Negeri Kencana 3 Bukit Cimanggu Bogor - Elly Sukmanasa (FKIP UNIVERSITAS PAKUAN, 2016)
The research aims at describing the implementation of School Based Management to improve the quality of education at Sekolah Dasar Negeri Kencana 3 Bukit Cimanggu City Kota bogor. The research was conducted at Sekolah Dasar Negeri Kencana 3 Bukit Cimanggu City with the considerations of the parents’ economic level, social and cultural backgrounds, the school’s facilities, the school’s age of being established and its achievement of being the pioneer of School Based Management. The focus of the research is to find out the supporting and inhibiting factors of the implementation of school based management to improve the quality of education, to look for solution of the inhibiting factors, to observe the planning, doing, and monitoring processes, to evaluate the inhibiting/supporting factors involving the headmaster, teachers, committee, and students’ supervisors. The process of organizing the program was aimed at establishing the vision, mission, and objectives of the school. In conducting the program of school based management, transparency, participation, and accountability are emphasized. The research result shows that the headmaster as the one responsible for the process of education at school had striven hard to build the atmosphere of togetherness and trust among teachers and school officers. It is in accordance with the principles of the program which are transparency, participation, and accountability.